Expression of dopamine D2 and D3 receptors in the human retina revealed by positron emission tomography and targeted mass spectrometry - Caravaggio, Fernando (Exp Eye Res, 2018)
Dopamine D(2) receptors (D(2)R) are expressed in the human retina and play an important role in the modulation of neural responses to light-adaptation. However, it is unknown whether dopamine D(3) receptors (D(3)R) are expressed in the human retina. Using positron emission tomography (PET), we have observed significant uptake of the D(3)R-preferring agonist radiotracer [(11)C]-(+)-PHNO into the retina of humans in vivo. This led us to examine whether [(11)C]-(+)-PHNO binding in the retina was quantifiable using reference tissue methods and if D(3)R are expressed in human post-mortem retinal tissue. [(11)C]-(+)-PHNO data from 49 healthy controls (mean age: 39.96 ± 14.36; 16 female) and 12 antipsychotic-naïve patients with schizophrenia (mean age: 25.75 ± 6.25; 4 female) were analyzed. We observed no differences in [(11)C]-(+)-PHNO binding in the retina between first-episode, drug-naïve patients with schizophrenia and healthy controls. Post-mortem retinal tissues from four healthy persons (mean age: 59.75 ± 9.11; 2 female) and four patients with schizophrenia (mean age: 54 ± 17.11; 2 female) were analyzed using a targeted mass spectrometry technique: parallel reaction monitoring (PRM) analysis. Using targeted mass spectrometry, we confirmed that D(3)R are expressed in human retinal tissue ex vivo. Notably, there was far greater expression of D(2)R relative to D(3)R in the healthy human retina (~12:1). Moreover, PRM analysis revealed reduced D(2)R, but not D(3)R, expression in the retinas of non-first episode patients with schizophrenia compared to healthy controls. We confirm that D(3)R are expressed in the human retina. Future studies are needed to determine what proportion of the [(11)C]-(+)-PHNO signal in the human retina in vivo is due to binding to D(3)R versus D(2)R. Knowledge that both D(2)R and D(3)R are expressed in the human retina, and potentially quantifiable in vivo using [(11)C]-(+)-PHNO, poses new research avenues for better understanding the role of retinal dopamine in human vision. This work may have important implications for elucidating pathophysiological and antipsychotic induced visual deficits in schizophrenia.